Growth and survival of giant gourami juvenile immersed in freshwater containing growth hormone - Pustika Ratnawati; . Alimuddin; Harton Arfah; Agus Oman Sudrajat (Jurnal Akuakultur Indonesia)
Growth of giant gourami is relatively slow. Administration of recombinant growth hormone (rGH) by several times immersion in water containing 0.9% NaCl for one hour can significantly increase the growth. In this study, giant gourami juvenile were immersed in freshwater containing 120 mg/L rGH to determine the long immersion time that provides higher growth and survival. Juvenile at seventh-day-old after egg yolk absorbed was immersed for 0.5, 1.0, 2.0, and 3.0 hours in rGH solution. As controls, fish was immersed in freshwater without rGH (control 1: C1), and water containing 0.9% NaCl, and 120 mg/L rGH (control 2: C2). Fish was kept under controlled conditions in 20 L aquarium for three weeks, then in 50 L aquarium until at end of experiment, and fed at satiation. The results showed that highest growth in body weight, survival, and biomass (p<0.05) were obtained in rGH immersion treatment for 0.5 hour. Biomass of fish immersed by rGH for 0.5 hour was about 32% higher compared to control C1, and 13% compared to C2. Survival of the 0.5 hour rGHimmersed fish (100%) was similar to control C1 and C2. Thus, immersion of giant gourami juvenile in freshwater containing rGH for 0.5 hour allowed highest growth rate, and this method is relatively easy to be adopted by fish hatchery.